TaqMan Quantitative-PCR Detection of Xylella taiwanensis in Taiwan - Su, Chiu-Chu; Fung, Jie-An; Chang, Ruey-Jang; Chang, Chung Jan; Jan, J F; Shih, Hsien-Tzung; Chen, Jianchi C (Plant disease, 2023)
Xylella taiwanensis (Xt) is a nutritionally fastidious bacterial pathogen causing pear leaf scorch disease (PLSD) in Taiwan. The disease causes early defoliation, loss of tree vigor and reduction in fruit yield and quality. No cure for PLSD is available. The only option for growers to control the disease is to use pathogen-free propagation material, which requires early and accurate detection of Xt. Currently, only one simplex PCR method is available for the diagnosis of PLSD. We developed five Xt-specific TaqMan quantitative PCR (TaqMan qPCR) systems (primers-probe sets) for detection of Xt. The PCR systems target three conserved genomic loci commonly used in bacterial pathogen detection: the 16S rRNA gene (rrs), the 16S-23S rRNA intergenic transcribed sequence (16S-23S rRNA ITS), and the DNA gyrase gene (gyrB). BLAST analysis using the GenBank nr sequence database, including whole genome sequences of 88 Xanthomonas campestris pv. campestris (Xcc) strains, 147 X. fastidiosa (Xf) strains, and 32 Xt strains, showed that all primer and probe sequences were specific only to Xt. Single nucleotide polymorphisms (SNPs) provided the primer/probe specificity to Xt. The PCR systems were evaluated by using DNA samples from pure cultures of two Xt strains, one Xf strain, one Xcc strain and 140 plant samples collected from 23 pear orchards in four counties in Taiwan. The two-copy rrs and 16S-23S rRNA ITS-based PCR systems (Xt803-F/R, Xt731-F/R, and Xt16S-F/R) showed higher detection sensitivity than the two single-copy gyrB-based systems (XtgB1-F/R and XtgB2-F/R). A metagenomic analysis of a representative PLSD leaf sample detected the presence of non-Xt proteobacteria and fungal pathogens that should be taken into consideration in PLSD, as they might interfere with diagnosis.